Physical Geology - Panchuk, Karla (Open textbook library., 2019)
Physical Geology is a comprehensive introductory text on the physical aspects of geology, including rocks and minerals, plate tectonics, earthquakes, volcanoes, mass wasting, climate change, planetary geology and much more. It has a strong emphasis on examples from western Canada. It is adapted from "Physical Geology" written by Steven Earle for the BCcampus Open Textbook Program.